2018
DOI: 10.1016/j.celrep.2018.01.052
|View full text |Cite
|
Sign up to set email alerts
|

PTPN2 Regulates Inflammasome Activation and Controls Onset of Intestinal Inflammation and Colon Cancer

Abstract: Variants in the gene locus encoding protein tyrosine phosphatase non-receptor type 2 (PTPN2) are associated with inflammatory disorders, including inflammatory bowel diseases, rheumatoid arthritis, and type 1 diabetes. The anti-inflammatory role of PTPN2 is highlighted by the fact that PTPN2-deficient mice die a few weeks after birth because of systemic inflammation and severe colitis. However, the tissues, cells, and molecular mechanisms that contribute to this phenotype remain unclear. Here, we demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
103
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(111 citation statements)
references
References 50 publications
8
103
0
Order By: Relevance
“…Therefore, further evaluations are needed to reveal the precise associations. Nevertheless, given the key role of VD 3 ‐PTPN2 in the response to inflammation, our results further support the previous suggestion that the therapeutic use of agents with anti‐cytokine properties such as VD 3 may provide outstanding benefits in the prevention and treatment of diabetic periodontitis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, further evaluations are needed to reveal the precise associations. Nevertheless, given the key role of VD 3 ‐PTPN2 in the response to inflammation, our results further support the previous suggestion that the therapeutic use of agents with anti‐cytokine properties such as VD 3 may provide outstanding benefits in the prevention and treatment of diabetic periodontitis.…”
Section: Discussionsupporting
confidence: 89%
“…The elevated levels of VDR and PTPN2 expression after VD 3 treatment could result in the downregulation of downstream proinflammatory proteins such as NF‐κB . The PTPN2 gene inhibits the expression of many proinflammatory genes by blocking JAK/STAT‐dependent signaling . Based on our previous animal studies, the present results further confirm the downregulated expression of PTPN2 and VDR in the gingival tissues of T2DCP patients, which could be considered as a pathophysiological effect of 25(OH)D 3 deficiency.…”
Section: Discussionsupporting
confidence: 82%
“…3j). This is in line with our previous finding that the regulation of IL-1β and IL-18 via PTPN2 is mediated via changes in protein activation, and not via changes in mRNA levels [18]. …”
Section: Resultssupporting
confidence: 93%
“…We have previously shown that loss of PTPN2 promotes activation of inflammasomes [18], and subsequent secretion of IL-1β and IL-18. Therefore, we also addressed whether loss of PTPN2 in epithelial cells affects expression of Il1b and Il18 mRNA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation